An analysis of tax avoidance of family companies in Indonesia - Dedi Rusdi; Edy Suprianto; Zaenal Alim Adiwijaya (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2023)
Taxes have an important role in building a country's economy. Therefore, as good citizens, we must pay taxes according to the regulations set by the government. This study aims to examine the effect of thin capitalization, executive characteristics, and transfer pricing on tax avoidance in family companies in Indonesia. This research uses quantitative methods. The data analysis technique used is descriptive statistical analysis. The population in this study consists of family companies listed on the Indonesia Stock Exchange in 2018-2020. This study used a purposive sampling technique with 317 family companies. Based on the analysis results, thin capitalization significantly affects tax avoidance; executive characteristics do not affect tax avoidance; transfer pricing does not affect tax avoidance. Therefore, further research needs to further analyze other variables outside the model in this study.